Czech Literary Classicism? - Turecek, Dalibor (Bohemica Olomucensia, 2016)
In the first step, the study deals with the use of the term "Classicism" in the Czech literary history. Thereafter, the possibilities of the new, methodologically modern model of this phenomenon are considered. The distinction of the permanently present latent notion of the "Classic" and the specific manifestations of them is suggested. These were realized in three clusters, different in their contexts, functions and poetics. Classicism, howewer, featured the important part of the Czech literature throughout the first half of the 19th century.
Keywords: Czech Literature; 18th and 19th Century; Classicism; Methodology of Literary History